An interpretive study of the English language needs of different stakeholders at Universitas Muhammadiyah Malang Indonesia - Poedjiastutie, Dwi (Curtin University, 2015)
This research examines the extent to which the curriculum in place at the English Department at the Universitas Muhammadiyah Malang addresses the stakeholders’ needs. By using a Needs Analysis a number of issues and problems were identified. In particular it was found that English programs should better prepare students for employment and post-university life, including future international collaboration and understanding English speaking people’s culture, and, for admission into higher education.